Comparison of efficacy and safety of intramuscular magnesium sulphate with low dose intravenous regimen in treatment of eclampsia - Haq, Aqsa Ikram ul; Naseem, Ulfat; Sadiq, Nadia; Batool, Syeda Maryam; Khalid, Tahira; Bashir, Shama (Journal of Rawalpindi Medical College, 2022)
INTRODUCTION: Eclampsia contributes to maternal mortality in developing, underdeveloped world. Various drugs have been tried to treat eclampsia. Magnesium sulphate has become the drug of choice due to various advantages and is associated with adverse outcome for both mother and fetus if not used correctly. OBJECTIVE: To compare the efficacy and safety of intramuscular magnesium sulphate with low dose intravenous regimen in treatment of eclampsia STUDY SETTING: The study was conducted at Gynecology and Obstetrics Department unit II, Holy Family Hospital, Rawalpindi, from June 20, 2020 to December 20, 2020. Study design was Randomized Controlled Trial. SUBJECTS & METHODS: Patients were randomly distributed into two groups, group-A (IM Group) and group-B (IV Group). Group-A patients received a loading dose of 4 gm IV MgSO4 over 5-10 minutes+10 gm MgSO4 deep intra-muscular injection (5 gm in each buttock) and a maintenance dose of 5 gm MgSO4 deep intramuscular injection in alternate buttock every 4 hourly. Group-B patients received MgSO4 4 gm slow IV over 5-10 minutes as loading dose and 1 gm MgSO4 per hour as continuous intravenous maintenance infusion. Clinical response to therapy for both drugs was calculated in terms of efficacy and safety. All the data were entered & analyzed by using SPSS v25.0. Both the groups were compared in terms of efficacy and safety by using Chi-Square test. A p-value less than 0.05 was taken as significant. RESULTS: A total of 160 patients with eclampsia were enrolled for this study. Patients were divided into two groups i.e. Group-A (IM MgSO4) and Group-B (IV MgSO4). In group-A, there were 45(56.3%) in 18-30 years age group and 35(43.8%) in 31-40 years age group, while in group-B, there were 48(60.0%) in 18-30 years age group and 32(40.0%) in 31-40 years age group. In IM MgSO4 group, prevention from recurrence of seizure was noted in 74(92.5%) and 78(97.5%) in IV MgSO4 group, which is statistically insignificant with a p-value of 0.147. CONCLUSION: Both IM and IV regimen are equally effective in controlling the recurrence of convulsions. IM Magnesium Sulphate is associated with a higher incidence of toxicity as evidenced by significantly higher incidence of loss of knee jerk reflex. Both IM and IV regimen are equally effective but IM Magnesium Sulphate is associated with a higher incidence of toxicity. KEY WORDS: Eclampsia, Intramuscular MgSO4, Intravenous MgSO4.